Socio-demographic determinants and prevalence of traditional medicine product use in Bali: implications for healthcare integration - Ni Made Umi Kartika Dewi; Sri Sulistyawati Anton; Dewi Puspita Apsari; Luh Seri Ani; Agung Wiwiek Indrayani; Pande Putu Januraga (Faculty of Pharmacy, Universitas Pancasila, 2026)
Traditional medicine products (TMPs) are integral to Balinese cultural practices. This study examined the socio-demographic determinants of TMP use through a cross-sectional survey of 440 households across all districts and cities in Bali province. A multistage cluster sampling method was applied, and data were collected using a structured questionnaire validated by expert review and tested for reliability (Cronbach’s alpha = 0.82). The results showed that 76.1% of the respondents used TMPs. The key predictors included age, gender, income, and residence. Middle-aged adults (46–55 years) had the highest odds of TMP use (OR = 5.667), followed by urban residents (OR = 4.999), individuals with no income (OR = 4.681), those earning below the provincial minimum wage (OR = 2.496), and women (OR = 1.838). These trends may be linked to cultural familiarity, financial barriers, caregiving roles, and increased product availability in urban areas. These findings underscore the need to integrate TMPs into Bali’s healthcare system through policy regulation, clinical guidelines, community education, and interprofessional training. Integration efforts must also address challenges such as regulatory oversight, product standardization, and patient safety. This study provides a foundation for developing culturally informed public health strategies to ensure the safe and effective use of TMP.